Pengaruh Metode Cooperative dan Self Esteem Terhadap Minat Kewirausahaan Pada Siswa Sma Kota Bekasi - Lusiana Wulansari; Paryono - (Jurnal Ilmiah Wahana Pendidikan, 2019)
Utilization of used goods needs to be calculated, in order to reduce and reduce pollution. Various ways have been done. School as a place of education can take shape and to realize the use of used goods that are of value to instill entrepreneurial interest in vocational students. The implementation method used is observation and demonstration. The results achieved, students are more independent and have the desire to process used goods, and then market it, via online..